Implementasi Marketing Mix pada Sosialisasi dan Pendampingan UMKM di Kelurahan Bulak, Surabaya - Izaroh, Shoqibatul; Muammar Alawi; Eka Putri Oktaviana; Nathania Aurell Manabung; Nurisma Bintang Kamilah; Abdul Aziz Mahmoud Effendi (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2026)
The success of MSMEs in marketing a product is determined by the implementation of effective branding. This is because strong branding can build a product brand perception among consumers, for example by utilizing increasingly advanced technology. However, MSMEs still lack understanding of the importance and strategies of branding. In Bulak Village, MSMEs still lack understanding of branding strategies, minimal product identity creativity, and limited use of social media as a promotional tool. As a concrete solution, an integrated branding program has been implemented in Bulak Village. This program includes MSME Branding-Marketing socialization, Menu Review sessions, and ongoing mentoring. This program aims to analyze the program's effectiveness in improving MSME performance. This activity uses a mixed method to collect data. Data were collected through direct observation and interviews of activities, as well as filling out forms (questionnaires) to obtain quantitative data on perceptions and performance. The results show that the branding socialization program significantly increased MSMEs' understanding of the importance of branding. Meanwhile, the mentoring program had a substantial positive impact on MSME performance, both in terms of product identity creativity and the use of promotional media.